The influence of after sales services on marketing performance in the retail sector in Botswana - Douglas Chiguvi (Dutch Journal of Finance and Management, 2020)
The focal point of the study was to investigate the influence of after sales services on marketing performance at Sefalana Holdings in Botswana. The study was conducted in order to find out the influence of after sales services on customer satisfaction, customer loyalty and customer retention at Sefalana Holdings in Botswana. Causal research approach was employed and a questionnaire was used to collect data from Sefalana customers. The study results indicated that after sales services are provided at Sefalana but they are not fully utilized and implemented. The study findings revealed that there is a weaker significant positive relationship between after sales services and customer satisfaction, customer loyalty and customer retention at Sefalana Holdings in Botswana. This infers that after sales services are not properly done at Sefalana and therefore, the researcher recommended that Sefalana Holdings should improve on the delivery of its after sales services in order to increase customer satisfaction, customer loyalty and customer retention.
Keywords: 650; after sales services; customer satisfaction; customer loyalty; customer retention